Far‐Field Superresolution Imaging via Spatial Frequency Modulation. Issue 11 (3rd September 2020) - Tang, Mingwei; Liu, Xiaowei; Wen, Zhong; Lin, Feihong; Meng, Chao; Liu, Xu; Ma, Yaoguang; Yang, Qing
Abstract: The diffraction limit substantially impedes the resolution of the conventional optical microscope. Under traditional illumination, the high‐spatial‐frequency light corresponding to the subwavelength information of objects is located in the near‐field in the form of evanescent waves, and thus not detectable by conventional far‐field objectives. Recent advances in nanomaterials and metamaterials provide new approaches to break this limitation by utilizing large‐wavevector evanescent waves. Here, a comprehensive review of this emerging and fast‐growing field is presented. The current superresolution imaging techniques based on evanescent‐wave‐assisted spatial frequency modulation, including hyperlens, microsphere lens, and evanescent field‐illuminated spatial frequency shift microscopy, are illustrated. They are promising in investigating unobserved details and processes in fields such as medicine, biology, and material research. Some current challenges and future possibilities of these superresolution methods are also discussed. Abstract : Recent advances in nanomaterials and metamaterials provide new approaches to break the diffraction limit by utilizing large‐wavevector evanescent waves. Here, the authors give a comprehensive review of this emerging and fast‐growing field from a new perspective: spatial frequency modulation (SFM). The current super‐resolution imaging techniques based on evanescent‐waves‐assisted SFM, including hyperlens, microsphere lens and evanescent fields illuminated microscopy are illustrated.